Glucocorticoid regulation of transcription at an amplified, episomal promoter. - Ostrowski, M C (1983)
The mouse mammary tumor virus long terminal repeat (MMTV LTR) has been introduced into cultured murine cells, using the 69% transforming fragment of bovine papilloma virus type 1 (BPV). Transformed cells contain up to 200 copies of the chimeric molecules per diploid genome. The restriction endonuclease map of the acquired recombinants, as well as the physical structure of the DNA, indicates that the LTR-BPV molecules present in these cells occur exclusively as unintegrated, extrachromosomal episome. When a 72-base pair direct repeat "enhancer" element (derived from the Harvey sarcoma retrovirus) was included in the MMTV LTR-BPV chimeric plasmids, DNA acquired through transfection, with a single exception, was integrated or rearranged or both. The transcriptional potential of the episomal MMTV promoter present in these cells was tested in two ways. First, steady-state levels of MMTV-initiated RNA were measured by quantitative S1 mapping. Second, the relative number of transcription complexes initiated in vivo was determined by using a subnuclear fraction highly enriched for MMTV-BPV minichromosomes in an in vitro transcription extension assay. Both approaches showed that the MMTV LTR present in the episomal state was capable of supporting glucocorticoid hormone-regulated transcription. We have therefore demonstrated the hormone response for the first time in a totally defined primary sequence environment. Significant differences both in the basal level of MMTV-initiated transcription and in the extent of glucocorticoid induction were observed in individual cell lines with similar episomal copy numbers. These phenotypic variations suggest that epigenetic structure is an important component of the mechanism of regulation.